Writing Pattern: an Investigation on The Essays of The Students of ELT Major - Putri, Hikmah Zalifah; Agustiani, Aulia; Rery, Nurul Masyithah (Universitas Pahlawan Tuanku Tambusai, 2025)
This article aimed to explore the writing pattern from writing academic essays by the students of ELT major. A content analysis was employed to find out the most common pattern shown in the essays of the participants. The data were the argumentative essays written by the students majoring in ELT as their course requirement to pass. The data were analyzed by looking at the common pattern shared amongst the essays which are (a) thesis statement, (b) coherency, and (c) concluding remark. The result of this research showed that participants shared similar writing pattern when it comes to writing an academic essay in English. They are, (1) broad or general thesis statement, (2) inconsistent use of pronoun when it comes to plural/singular nouns, and (3) additional and unnecessary information/topic in the concluding remark.